Stimulation of macrophages by Bacillus firmus: production of nitric oxide and cytokines - Zidek, Z; Tucková, L; Mára, M; Barot-Ciorbaru, R; Prokesová, L; Tlaskalová-Hogenová, H (International journal of immunopharmacology, 1998)
Immunostimulatory properties of gram-positive Bacillus firmus were investigated under in vitro conditions using murine peritoneal macrophages. B. firmus stimulated in a concentration and time dependent manner the secretion of tumour necrosis factor-alpha (TNF-alpha) and interleukin-10 (IL-10), but it had no influence upon interferon-gamma (IFN-gamma) and interleukin-2 (IL-2) production. It also substantially augmented production of nitric oxide (NO) induced by exogenous IFN-gamma. Inhibitory experiments using neutralizing antibodies against TNF-alpha and/or IL-10 have demonstrated that these cytokines are responsible for triggering the underlying mechanism(s) leading to enhanced NO production. The cytokine-stimulatory and NO-costimulatory properties could participate in the antiinfectious and anticancer effects of B. firmus, detected previously in the in vivo experiments.
Keywords: interferon gama; Interleukin-2; Interferon-gamma; Nitric Oxide Synthase; Bacillus; Tumor Necrosis Factor-alpha; Lipopolysaccharides; rekombinantní proteiny; Macrophage Activation; monoklonální protilátky; myši inbrední C57BL; interleukin-10; Antibodies, Monoclonal; aktivace makrofágů; Mice; TNF-alfa; interleukin-2; Macrophages, Peritoneal; synthasa oxidu dusnatého; ženské pohlaví; zvířata; oxid dusnatý; peritoneální makrofágy; lipopolysacharidy; Nitric Oxide; myši; Nocardia; Interleukin-10; Female; Mice, Inbred C57BL; Recombinant Proteins; Animals